STUDI PEMANFAATAN FASILITAS PANGKALAN PENDARATAN IKAN PAGURAWAN DI DESA NENASSIAM KECAMATAN MEDANG DERAS KABUPATEN BATUBARA PROVINSI SUMATERA UTARA - Puspa Dewi Primsa; Jonny Zain; Ronal M (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A series survey activity was conducted for obtaining information oncondition and existence of Pagurawan fishing port facilities at Nenassiam village,Medan Deras district, Batubara regency, North Sumatera province, as well as toinvestigate type and capacity of the facilities. All of the information is useful forevaluating the utilization level of the facilities. The result show that the utilizationof jetty was 817.32%, 86.17% for maneuverability area, 22.86% for depth ofmaneuverability area, and 51% for fish market hall. According to SWOT analysis,the Pagurawan fishing port stands on first quadrant, and it’s potentially to bedeveloped in future.Keywords: Facilities, fish market hall, maneuverability area, Pangurawanfishing port.